2011
DOI: 10.1099/vir.0.028340-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete coding sequences and phylogenetic analysis of porcine bocavirus

Abstract: Here we report, for the first time, the nearly full-length genome sequence of porcine bocavirus (PBoV), a recently discovered parvovirus from pigs. Phylogenetic trees based on this genome sequence showed that PBoV belongs to the branch containing the genus Bocavirus, which comprises canine minute virus (CnMV), bovine parvovirus, gorilla bocavirus and human bocavirus (HBoV), and was most closely related to the group containing CnMV. PBoV was predicted to contain three potential ORFs encoding the non-structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 18 publications
1
49
0
Order By: Relevance
“…The full genome of this virus was not obtained at that time, only a 1879 nucleotide (nt) long sequence, but based on similarities with the other bocavirus sequences it was named porcine boca-like virus (PBo-likeV). A very recent study of PBo-likeV reported the nearly full-length genome of this virus [13] and phylogenetic analysis confirmed that PBo-likeV belonged into the Bocavirus genus. A tentative classification of the newly discovered porcine bocaviruses was proposed by Zhang et al [14] grouping the six reported porcine bocaviruses into four species: PoBoV1 (porcine boca-like virus or PBoLV), PoBoV2 (porcine parvovirus 4 or PPV4), PoBoV3 (PBoV1/PBoV2), and PoBoV4 (6V/ 7V).…”
mentioning
confidence: 68%
“…The full genome of this virus was not obtained at that time, only a 1879 nucleotide (nt) long sequence, but based on similarities with the other bocavirus sequences it was named porcine boca-like virus (PBo-likeV). A very recent study of PBo-likeV reported the nearly full-length genome of this virus [13] and phylogenetic analysis confirmed that PBo-likeV belonged into the Bocavirus genus. A tentative classification of the newly discovered porcine bocaviruses was proposed by Zhang et al [14] grouping the six reported porcine bocaviruses into four species: PoBoV1 (porcine boca-like virus or PBoLV), PoBoV2 (porcine parvovirus 4 or PPV4), PoBoV3 (PBoV1/PBoV2), and PoBoV4 (6V/ 7V).…”
mentioning
confidence: 68%
“…Individual infection of PBoV usually causes no apparent clinical signs, and the co-infection of PBoV could make the clinical signs more obvious (Kesebir et al, 2006). Many scientists have also reported that PBoV exhibit varying prevalence rates with a wide range from 1.5% to 88% in pig samples from different regions (Blomstrom et al, 2009(Blomstrom et al, , 2010Zhai et al, 2010;Cadar et al, 2011;Li et al, 2011;McKillen et al, 2011;Shan et al, 2011a;Zeng et al, 2011;Zhang et al, 2011). In the present manuscript, compared with other organs in Chinese samples, the spleen (20.8%) and inguinal lymph node (27.2%) have much higher positive rates, suggesting that they are organs in which PBoV replication likely easily takes place.…”
Section: Discussionmentioning
confidence: 99%
“…a highly conserved alternative splice site and a putative secretory phospholipase A2 (sPLA2) motif in the NS1 and VP1 genes, respectively Zeng et al, 2011). PBoV has a much higher infection rate in diseased pigs than in healthy pigs, and post-weaning piglets are often co-infected with PCV2, PRRSV and PTTV2, which had a significantly higher prevalence in the PBoVpositive samples than that in the PBoV-negative samples .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies reported the nearly complete genome characterization of two species of PBoVs in China, PBoV1 and PBoV2 (7,12,(15)(16)(17). In recent studies, two new species of porcine bocaviruses (PBoV3 and PBoV4) were discovered in Northern Ireland and Hong Kong (11,14).…”
mentioning
confidence: 99%